2020
DOI: 10.1039/c9nr09024j
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between in situ structural and optical characterization of the semiconductor-to-metal phase transition of VO2 thin films on sapphire

Abstract: In situ XRD and IR optical measurements demonstrate the coexistence of M1 and R phases during the SMT transition of VO2 thin films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 78 publications
2
25
0
Order By: Relevance
“…We performed numerical evaluation of the derivatives of the emissivity curves. Critical temperatures, corresponding to the points of minimum for the derivatives, were found to be T c (heating) = 73 °C and a T c (cooling) = 66 °C, in agreement with literature results 19 .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We performed numerical evaluation of the derivatives of the emissivity curves. Critical temperatures, corresponding to the points of minimum for the derivatives, were found to be T c (heating) = 73 °C and a T c (cooling) = 66 °C, in agreement with literature results 19 .…”
Section: Resultssupporting
confidence: 90%
“…More specifically, in Ref. 19 is shown that an enlargement of the hysteresis loop is observed due to the size dispersion of the crystallites and a progressive increase of the thermal hysteresis width is observed with the decrease of the thickness of the VO 2 , that can be related to the formation of VO 2 crystallites with smaller domains 19 .…”
Section: Discussionmentioning
confidence: 96%
“…Heterostructures, through the incorporation of distinct semiconductor and/or metal nanostructures, have emerged as the extensive investigations arisen from their innovative and superior optoelectronic [1,2], mechanic [3], and optical [4][5][6][7] properties, which further lead to the substantial improvement of various applications, ranging from photodetectors [8][9][10][11], solar cells [12][13][14], optical communications [15], to biological detection [16]. In the practical regard, nevertheless, the synthetic method of heterostructures turn out to be critical for attaining the requirement of manufacturing standards such as large production, simple procedure and sound reliability.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we aim to collect information and improve knowledge about the behavior of TMOs in solar cells by applying MoO3 and WO3 as selective hole contacts in c-Si HJT. First, we investigated the optical properties of MoO3 and WO3 layers deposited on quartz substrates by means of Pulsed Laser Deposition (PLD), a technique that allows obtaining a controllable and reproducible deposition of a broad number of metal oxides [10]- [18]. Then we used the same process to fabricate the TMO-based hole selective contact in solar cell prototypes based on n-type nanocrystalline silicon oxide [19].…”
Section: Introductionmentioning
confidence: 99%